2021
DOI: 10.1002/csc2.20617
|View full text |Cite
|
Sign up to set email alerts
|

Shade and nitrogen fertilization affect forage accumulation and nutritive value of C4 grasses differing in growth habit

Abstract: Light reduction in silvopastoral systems and self‐shading in treeless grasslands can lead to shade‐avoidance responses by tropical grasses. Light environment in association with nitrogen (N) supply influence the growth and nutritive value of forage grasses. This study aimed to quantify forage accumulation (FA) and forage nutritive value of tropical grasses differing in growth habit in environments with contrasting light and N resources. A field study was conducted using ‘Jiggs’ bermudagrass [Cynodon dactylon (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
2
2
0
Order By: Relevance
“…These results together with pasture stem height and leaf height may potentially explain the vertical distribution of nutritive values in the overall sward. Generally, results of the present study supported the hypothesis that BM outperformed the other two species in quality parameters in relation to the leaf, stem, and whole plant, which was in agreement with a number of other studies [2,46,47,51,60]. The reason for BM producing relatively higher quality herbage is predominantly associated with its plant morphological composition (high leaf: stem) [10].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results together with pasture stem height and leaf height may potentially explain the vertical distribution of nutritive values in the overall sward. Generally, results of the present study supported the hypothesis that BM outperformed the other two species in quality parameters in relation to the leaf, stem, and whole plant, which was in agreement with a number of other studies [2,46,47,51,60]. The reason for BM producing relatively higher quality herbage is predominantly associated with its plant morphological composition (high leaf: stem) [10].…”
Section: Discussionsupporting
confidence: 92%
“…Pasture canopy structure is partly determined by genetics and is expected to vary within genotypes. Brachiaria Mulato II is an improved Brachiaria hybrid developed to produce quality herbage for livestock [10,49], and observed canopy structure parameters of the present study confirmed its superior agronomic performances reported in other tropical and subtropical areas around the world [13,[46][47][48][50][51][52]. In addition, the higher forage yield of GP explains the forage-yielding potential of the genus megathyrsus explained elsewhere [2].…”
Section: Discussionsupporting
confidence: 79%
“…The FA and forage nutritive value are generally affected by pre‐graze canopy height, and when associated with an adequate N supply (Moreno et al, 2022; Pontes et al, 2017) may allow for a greater stocking rate (Gurgel et al, 2020). Greater N inputs (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The gray correlation analysis and the dry matter yield of forage stem and leaf traits showed leaf area, stem diameter, and leaf length were the top three stem and leaf traits that contributed more to the dry matter yield of alfalfa [40]. The slower-growing species in the mixed sowing system were affected by the shade effect because shade strongly affects the development of forages by changing their biomass allocation strategy and reducing the growth height of the forage [41][42][43]. The stem length of awnless brome contributed more to its dry matter yield than stem diameter, suggesting that adequate light resources increase the dry matter yield of awnless brome.…”
Section: Effects Of Different Stem and Leaf Traits On Forage Yield Tr...mentioning
confidence: 99%